2020
DOI: 10.7150/thno.38736
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-on-a-chip mimicking the progression of kidney cancer in the liver for predicting treatment efficacy

Abstract: Metastasis is one of the most important factors that lead to poor prognosis in cancer patients, and effective suppression of the growth of primary cancer cells in a metastatic site is paramount in averting cancer progression. However, there is a lack of biomimetic three-dimensional (3D) in vitro models that can closely mimic the continuous growth of metastatic cancer cells in an organ-specific extracellular microenvironment (ECM) for assessing effective therapeutic strategies.Methods: In this metastatic tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 44 publications
1
75
0
Order By: Relevance
“…Another idea that has gained immense popularity amongst organ chip researchers is the idea of a human-on-a-chip (Wang et al, 2020). This model aims to examine normal human physiology within a microfluidic system by combining single organ chip designs into a multi-organ chip design that allows the organs to work in conjunction with each other much like organs in the human body do (Wang et al, 2020). MOC and a complete human-on-a-chip design would allow for cheaper and more effective drug testing and thus would greatly benefit biomedical sectors (Wang et al, 2020).…”
Section: Advancement In Real-time Visualization Via Microfluidic Systmentioning
confidence: 99%
See 2 more Smart Citations
“…Another idea that has gained immense popularity amongst organ chip researchers is the idea of a human-on-a-chip (Wang et al, 2020). This model aims to examine normal human physiology within a microfluidic system by combining single organ chip designs into a multi-organ chip design that allows the organs to work in conjunction with each other much like organs in the human body do (Wang et al, 2020). MOC and a complete human-on-a-chip design would allow for cheaper and more effective drug testing and thus would greatly benefit biomedical sectors (Wang et al, 2020).…”
Section: Advancement In Real-time Visualization Via Microfluidic Systmentioning
confidence: 99%
“…A scrupulous investigation was conducted that aimed to mimic the progression of kidney cancer via a novel 3D metastatic cancer cell model (Wang et al, 2020). Previous metastatic cancer models have been created culturing cells in 3D but lacked the ability to interact with the correct physiopathological conditions as well as accurately reflect the effect of anticancer drugs in vivo (Wang et al, 2020). A 3D biomimetic liver microtissue modeled in DLM/GelMA hydrogel and subjected to continuous perfusion was used to culture the kidney cancer cells (Caki-1) (Wang et al, 2020).…”
Section: Tumor Models and Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…To model liver metastasis, gelatin methacryloyl was combined with decellularized liver matrix components including bioactive factors derived from liver matrix, in a dynamic culture system to assess drug-dose responses to acetaminophen and sorafenib ( Lu et al, 2018 ). In a similar metastasis-on-a-chip model of kidney cancer metastasized to the liver, NP-conjugated 5-fluorouracil was shown to be more efficacious than free drug ( Wang et al, 2020 ).…”
Section: Three-dimensional In Vitro Andmentioning
confidence: 99%
“…Therefore, this platform was considered to be a promising tool for cardiac pathophysiological study and drug screening [95]. Wang et al [96] reported a microfluidic tumor progression model based on metastasis-on-a-chip. Decellularized liver matrix (DLM)/GelMA (ratio 2:3) hydrogel was assembled on the chip to serve as a 3-D biomimetic liver microenvironment to culture kidney cancer cells (Caki-1) to mimic the progression of metastatic kidney cancer, as shown in Figure 7.…”
Section: Components For Organs-on-a-chipmentioning
confidence: 99%